Comparing the accuracy of ultrasound versus fluoroscopy in glenohumeral injections: A systematic review and meta‐analysis. Issue 7 (25th March 2014) - Amber, Kyle T.; Landy, David C.; Amber, Ian; Knopf, David; Guerra, Jorge
ABSTRACT Objective We performed a systematic review with meta‐analysis to compare the accuracy of fluoroscopic‐guided glenohumeral injections with that of ultrasound‐guided glenohumeral injections as reported in prior studies. Methods We reviewed the databases of MEDLINE, PubMed, and Google Scholar using combinations of the keywords "ultrasound, " "fluoroscopy, " "injection, " and "shoulder" for articles reporting the injection accuracy, confirmed by imaging, of the first attempt under either fluoroscopic or ultrasound guidance. A meta‐analysis was performed to assess the accuracy of fluoroscopic‐guided glenohumeral injections versus ultrasound‐guided glenohumeral injections. Results Five of 42 pertinent studies met our inclusion criteria for a total of 406 glenohumeral injections, of which 115 were fluoroscopy‐guided and 291 were ultrasound‐guided. The meta‐effect estimates for the proportion of joints successfully injected with ultrasound and fluoroscopic guidance were 93% (95% CI, 86% to 98%) and 80% (95% CI, 63% to 93%), respectively, which did not reach statistical significance (Q[df] = 2.55 [1], p = 0.11). Conclusions Our meta‐analysis indicates that glenohumeral injections guided by ultrasound are more accurate than injections guided by fluoroscopy but this difference did not reach statistical significance. As the use of ultrasound does not expose the patient or practitioner to radiation, its similar accuracy may make it the preferred modality for image‐guided glenohumeral joint injections. Limitations to our analysis include the retrospective nature, limited number of studies included, and the potential generalizability of our findings to regions outside of those included in our study. © 2014 Wiley Periodicals, Inc. J Clin Ultrasound42:411–416, 2014